LIVING THE HEALTH PROMOTION IN THE FAMILY HEALTH STRATEGY (Fiep Bulletin - online, 2011)
The aim of this study was to report an experience during the internship in the Basic Family Health Felipe Shrimp, Natal / RN. This is a unique situation involving a teenager with developmental delay. The first contact with M. D. S occurred via a home visit performed, as requested by the health officer of the area, due to an attack of scabies in which the teenager is going through. However, on reaching the place, it was apparent that the situation was far beyond that. The contact with the teenager prompted further investigation of the case, aiming at acquiring knowledge and, if possible, interventions that provide better quality of life of the user. From experience it was observed that people with disabilities represent a significant portion of the population and so the nursing staff must be prepared to provide a holistic care to these people, preferably involving a multidisciplinary team. This is done by combining scientific knowledge and technological skills of observation, communication and intuição.Diante addition, it is evident the importance of completing this experience report. This activity was a way to know more about this special portion of the population that normally is not discussed as their importance demands.
Keywords: Family Health Strategy; adolescence; scabies